Writing, Editing and Publishing an Article in a Scientific Journal - Khattri, Man Bahadur (Dhaulagiri Journal of Sociology and Anthropology, 2010)
The purpose of this article is to discuss some important aspects involved while writing an article to publish in a scientific journal. This is a review article. I argue that writing an article is technical as well as creative art of an author which facilitates acceptance of article for publication in a scientific journal. Academicians are obliged to conduct research and publish articles to demonstrate their job efficiency. To publish an article in a scientific journal is the first necessary condition to meet standard norms i.e. journal’s guideline for authors and the next is to follow the editing processes of the journal. Writing an article for printed version is becoming an old fashion. Therefore, authors need to learn how to submit a scholarly written article online and follow review processes. Writing and publishing of a scientific article is not only important for individuals and specific scientific community, it is also important to the wider society which helps to enhance stock of knowledge, and sharing and learning culture. Key words: Online publication; author aid; open access; copy editing; peer review DOI: 10.3126/dsaj.v3i0.2787 Dhaulagiri Journal of Sociology and Anthropology Vol.3 2009 185-196